Care pathways for organ donation after brain death: guidance from available literature?. (19th July 2016) - Hoste, Pieter; Vanhaecht, Kris; Ferdinande, Patrick; Rogiers, Xavier; Eeckloo, Kristof; Blot, Stijn; Hoste, Eric; Vogelaers, Dirk; Vandewoude, Koenraad
Abstract: Aims: A discussion of the literature concerning the impact of care pathways in the complex and by definition multidisciplinary process of organ donation following brain death. Background: Enhancing the quality and safety of organs for transplantation has become a central concern for governmental and professional organizations. At the local hospital level, a donor coordinator can use a range of interventions to improve the donation and procurement process. Care pathways have been proven to represent an effective intervention in several settings for optimizing processes and outcomes. Design: A discussion paper. Data sources: A systematic review of the Medline, CINAHL, EMBASE and The Cochrane Library databases was conducted for articles published until June 2015, using the keywords donation after brain death and care pathways. Each paper was reviewed to investigate the effects of existing care pathways for donation after brain death. An additional search for unpublished information was conducted. Discussion: Although literature supports care pathways as an effective intervention in several settings, few studies have explored its use and effectiveness for complex care processes such as donation after brain death. Implications for nursing: Nurses should be aware of their role in the donation process. Care pathways have the potential to support them, but their effectiveness has been insufficiently explored. Conclusion: Further research should focus on the development and standardization of the clinical content of a care pathway for donation after brain death and the identification of quality indicators. These should be used in a prospective effectiveness assessment of the proposed pathway.